Soil fertility status, carbon and nitrogen stocks under cover crops and tillage regimes - Carvalho, Arminda; Marchão, Robélio; Souza, Kleberson; Bustamante, Mercedes Maria (Revista Ciência Agronômica, 2014)
The aim of the present study was to evaluate the effects of cover crops on the soil’s chemical fertility, in particular its carbon and nitrogen content, in a Typic Acrustox under conventional and no-tillage corn systems. We hypothesized that the no-tillage system associates with cover crops maintains or increases soil carbon and nitrogen stocks and enhance soil fertility. The no-tillage system did not present higher carbon and nitrogen stocks than conventional tillage, but resulted in higher concentrations of exchangeable bases, higher CEC, and higher base saturation in the surface soil layer, mainly under use of Canavalia brasiliensis. Carbon and nitrogen stocks (up to 40 cm depth) differ significantly between the different cover crop species. The use of Mucuna pruriens and Canavalia brasiliensis allows maintain or increase soil C and N stocks. The no-tillage system results in higher accumulation of soil organic matter (0-5 cm), and appears very likely to enhance soil fertility. The use of Canavalia brasiliensis and Mucuna pruriens in succession to corn promotes carbon sequestration and can be used to enhance soil quality in Cerrado agroecosystems.